Repositioning Karya Persatuan Penyandang Disabilitas Indonesia (PPDI) Kota Padang dengan Strategi IMC dan Standarisasi Produk - Dessy Kurnia Sari; Donard Games; Danny Hidayat; Widya Hapsari; Ana Ardiana (Warta Pengabdian Andalas, 2019)
Our community often underestimates people with disabilities including products that they were produced. This is very unfortunate. Persons with disabilities have a right to be accepted in a society. Therefore, some lecturers and students from Universitas Andalas in collaboration with the Association of Indonesian People with Disabilities, abbreviated as PPDI and the Association of Women with Disabilities (HWDI) agreed to manage quality and marketing aspects of products made by people with disabilities. This community service activity leads to the formulation of the Integrated Marketing Communication (IMC) strategy to strengthen product image created by people with disabilities who are also member of PPDI and HWDI. Besides that, the team also implemented a product standardization strategy. People with disabilities were trained to produce a good and standardized product that met expecation of their target market. Online marketing platforms were also used in promoting the high qualities ethnic souvenir produced by people with disabilities.